Warisan Pendidikan Islam di Banyumas: Sejarah dan Kontribusi Pondok Pesantren Al Anwar Bogangin, Sumpiuh - Syibromalisi , Alwi Akhmad; Damayanti , Alfina; Kristiana, Desi Ayu; Robbani, Rifqi Ahmad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
Islamic education in Indonesia has deep historical roots, one of which is through pesantren institutions that play a vital role in preserving, developing, and transforming Islamic values within society. Pondok Pesantren Al Anwar Bogangin, located in Sumpiuh District, Banyumas Regency, is one of the traditional pesantren that has made significant contributions to the development of Islamic education in the region. This study aims to explore the historical background of the establishment of Pondok Pesantren Al Anwar Bogangin and to analyze its contributions in the fields of education, social engagement, and Islamic dakwah in Banyumas. The method used in this study is a literature review, examining various written sources such as local historical books, pesantren archives, scholarly articles, and other relevant supporting documents. The findings of this research show that Pondok Pesantren Al Anwar Bogangin serves not only as a center of religious education for the surrounding community, but also plays a significant role in producing moderate religious scholars and community leaders. Moreover, this pesantren helps maintain the continuity of classical Islamic scholarly traditions, rooted in the study of traditional Islamic texts (kitab kuning) and the implementation of the sorogan and bandongan learning systems. Its social contributions are reflected in various community activities and the active roles of its students and alumni in fostering the spiritual and moral development of Banyumas society.